2021
DOI: 10.18331/brj2021.8.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size of cerium oxide nanoparticles on the combustion behavior and exhaust emissions of a diesel engine powered by biodiesel/diesel blend

Abstract: Meeting the emission norms specified by governing bodies is one of the major challenges faced by engine manufacturers, especially without sacrificing engine performance and fuel economy. Several methods and techniques are being used globally to reduce engine emissions. Even though emissions can be reduced, doing so usually entails a deterioration in performance. To address this problem, nanoadditives such as cerium oxide (CeO2) nanoparticles are used to reduce engine emissions while improving engine performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…With the increase in NP size, it is observed that the SFC is slightly higher. It has been shown that larger sized NPs have lower thermal conductivity [ 69 ] and higher fuel viscosity. The lower thermal conductivity and higher viscosity of larger NPs cause poor atomization, mixing, and combustion characteristics, which increases the SFC.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase in NP size, it is observed that the SFC is slightly higher. It has been shown that larger sized NPs have lower thermal conductivity [ 69 ] and higher fuel viscosity. The lower thermal conductivity and higher viscosity of larger NPs cause poor atomization, mixing, and combustion characteristics, which increases the SFC.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the uncertainty of the dependent variable was calculated using the errors involved in measuring independent parameters using Eq. ( 7) [48]. 4 is a graph of specific fuel consumption.…”
Section: Methodsmentioning
confidence: 99%
“…However, HRR is reported to lower with the inclusion of Al 2 O 3 NP with diesel‐JME blend (B20) at a dosage level of 30 ppm, 40 diesel‐PGME blend (B25) at dosage levels of 50 and 100 ppm, 82 diesel‐PLOME blend (B20) at a dosage level of 30 mg/L, 154 diesel‐JOME‐ethanol blend (D70B10E20) at dosage levels of 15–100 mg/L, 145 water‐diesel emulsion (D83W15) at a dosage level of 100 ppm, 90 CME‐water emulsion (B83W15) at a dosage level of 100 ppm, 91 diesel‐PLOME blend (B20) at a dosage level of 30 mg/L, 154 and diesel‐ethanol blend (E10) at a dosage level of 100 ppm 88 compared to fuel with no Al 2 O 3 NP additive. Addition of CeO 2 NP to diesel‐WCOME blend (B20) at a 80 ppm dosage level, 43 diesel‐WCOME blend (B30) at a dosage level of 90 ppm, 155 RME (B5)‐water emulsion at dosage of 90 ppm, 96 and diesel‐JME‐ethanol blend (D80B15E4) at a doping level of 100 mg/L 157 led to enhanced HRR. However, HRR is decreased with the inclusion of CeO 2 NP with LGO‐water emulsion (O93W5) at 30 ppm dosage level 36 and diesel‐castor oil methyl ester (COME)‐ethanol blend (D70B10E20) at a dosage level of 25 ppm 156 .…”
Section: Effect Of Metal Based Nanoadditive On Combustion Characteris...mentioning
confidence: 99%
“…100 ppm CeO 2 NP doped diesel‐MME blend (B20) decreased smoke emission by 8% compared to neat diesel 94 . In addition, 80 ppm CeO 2 NP doped waste cooking oil biodiesel blend (B20) enormously lowered smoke emission of a single cylinder, water cooled, Kirloskar TV1, CI engine by 53% 43 . Inclusion of CuO NP at 50 ppm dosage level with B20 blend of mahua biodiesel lowered smoke emission up to 12.5% 64 .…”
Section: Effect Of Metal Based Nanoadditive On Emission Characteristicsmentioning
confidence: 99%